Hybrid Learning Management at Sekolah Indonesia Riyadh: Challenges and Optimization Strategies - Subianto Karoso; Khabib Muzari (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the effectiveness of managing hybrid distance learning (HDL) at Sekolah Indonesia Riyadh (SIR), an international educational institution serving the Indonesian community in Saudi Arabia. Combining online and face-to-face teaching methods, the research explores the managerial strategies employed, challenges encountered, and their impact on the learning process and outcomes. A qualitative descriptive method with a case study approach was utilized. Data were collected through semi-structured interviews, participatory observations, and document analysis. The findings indicate that the success of the hybrid model at SIR is influenced by the readiness of technological infrastructure, teachers' competence in utilizing digital platforms, and active parental involvement. However, resource limitations, digital divides, and coordination barriers pose significant challenges. The study recommends continuous teacher training, enhancement of technological infrastructure, and closer collaboration between schools and parents. These findings provide insights for other educational institutions to develop effective and sustainable hybrid learning strategies.